Inactivation of Antibiotic Resistant Bacteria in Hospital Wastewater by Tio2/h2o2 Photocatalysis - Raul B. Aranciaga Pajuelo; Jonathan P. Vargas Lopez; Carlos Castaneda Olivera; Jorge L. Jave Nakayo; Elmer G. Benites Alfaro; Carlos F. Cabrera Carranza (Chemical Engineering Transactions, 2021)
Contamination of wastewater by drug-resistant bacteria is an emerging problem because it can have a direct effect on human health and the environment. Therefore, this research determined the photocatalytic efficiency of TiO2 and H2O2 in the inactivation of Escherichia coli (E. coli) and intestinal Enterococci (intestinal E.) bacteria. The tests were carried out in two photoreactors of 12 L each, achieving a percentage of efficiency of 75.90% and 93.01% in the inactivation of Escherichia coli and intestinal Enterococci, respectively, with a dose of 500 mg/L of TiO2 and 100 mg/L of H2O2. In addition, a higher percentage of efficiency in the inactivation of intestinal Enterococci was evidenced with respect to Escherichia coli, and the chemical and physical parameters of the wastewater improved with photocatalytic treatment, reaching values below the Maximum Allowable Values for non-domestic wastewater discharges. Finally, the results obtained showed that photocatalysis as a wastewater treatment method for the inactivation of antibiotic-resistant bacteria is efficient and could be used as an alternative to treat hospital wastewater.